At the crossroads of pedagogical change in higher education - Burdick, Melanie N.; Hallman, Heidi L. (Routledge, 2022)
"This book explores pedagogical change and innovation in U.S. colleges and universities and how faculty are prepared to adapt to such changes. Drawing from interviews with faculty developers at Centers for Teaching and Learning at research and teaching-focused institutions across the U.S., this book explores how traditional forms of pedagogy are shifting toward student-centered and student-directed forms of learning. The book unpacks the historical development of changes in teaching, drawing from research in teaching within particular domains such as diversity, equity, and inclusion in higher education, community-based teaching and learning, online and hybrid teaching and learning, course design, interdisciplinary teaching and learning, assessment of teaching, and the scholarship of Teaching and Learning (SoTL). This is an invaluable resource for faculty, graduate students and scholars of Higher Education, and Faculty Developers looking to promote a culture of continual renewal and innovation at their institutions"--
Foreword by Nancy Chick -- Preface -- Acknowledgements -- Introduction: teaching as an important mission of higher education -- Institutionalizing centers for teaching and learning -- The scholarship of teaching and learning and faculty learning communities: variations on a theme -- Collaborative and interdisciplinary faculty learning -- Diversity, equity, and inclusion: more training and more ambiguity -- Shifts in form, content, and communication: the rise of online, hybrid, and hyflex learning -- From content expert to content curator: course design and universal design for learning -- Stepping into the fray: faculty development and the assessment of teaching -- Faculty development and faculty developers now: at the crossroads of pedagogical change.
Keywords: Education, Higher; Culturally relevant pedagogy; Educational change; Student-centered learning